Family planning impact evaluation: the evolution of techniques - Albert I. Hermalin (Población y Salud en Mesoamérica)
This paper is a slightly revised version of a paper prepared for the seminar on methods for impact evaluation of family planning programs held in Jaco, Costa Rica, May 14-16, 1997. The seminar was sponsored by the International Union for the Scientific Study of Population (IUSSP), the United States Agency for International Development (USAID), the Carolina Population Center of the University of North Carolina, and the Central American Population Program of the University of Costa Rica.